Tinjauan Pengelolaan Indeks Penyakit Rawat Inap di RSU Aro Pekalongan - Pikriyatul Munawaroh; Asih Prasetyowati; Nur Asia Hapsari; M. Nasrul Latif (STIKES HAKLI Semarang, 2023)
Index in medical records services means a list of important words or terms arranged according to a specific procedure for the purpose of retrieval. Meanwhile, indexing according to Permenkes RI No. 24 of 2022 Article 18 is a data grouping activity in the form of at least an index of patient names, addresses, types of diseases, actions or operations, and deaths. One of the indices in RSU ARO Pekalongan is a disease index. Disease index is an index about a certain type of disease that has been assigned a diagnosis by a doctor and a disease diagnosis code by a medical recorder. This study is descriptive using the retrospective study method. The object in this study is the inpatient disease index at RSU ARO Pekalongan and the subject in this study is the Indexing officer at RSU ARO Pekalongan. Primary data sources are obtained through observation and interviews with indexing officers and medical record heads, while secondary data are obtained by looking directly at disease index table data. Creating an index that already uses a computer and disease index data that lists the major, second and complication diagnoses. Inpatient disease index management is good, but still semi-manual, it should be necessary to develop SIMRS that is integrated with patient index data management. Inpatient disease index data should be used as a basis for drug planning by improving the integrity or sustainability of existing SIMRS.